The Effect of Mangosteen Rind Extract (Garcinia mangostana L) to the Damaging of Hepar Cell of Mice (Mus musculus) Induced by Paracetamol - Winda A Panjaitan; S B Widjokongko; Sigit Setyawan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: The antioxidant properties of mangosteen rind extract such as xanthones, vitamin B1, vitamin B2, and vitamin C are estimated can protect hepar from free radicals and reducing NAPQI which produced by paracetamol metabolism. The purpose of this research is to know the effect of mangosteen rind ethanol extract to the damaging of hepar cell of mice induced by paracetamol. Methods: This research was a laboratorial experiment with post test only control group design. Samples of 28 male mice, Swiss webster type, 2-3 months old age and 20 gram of each weight, were divided into 4 groups in random or 7 mice each group. Aquadest were administered to mice in Control Group (KK) and the First Treatment Group (KP1), while mangosteen rind extract were administered to the Second Treatment Group (KP2) and the Third Treatment Group (KP3) with the dose of 10 mg/20 g body weight of mice and 15 mg/20 g body weight of mice. Paracetamol were administered to KP1, KP2, KP3, with dose 5.07 mg/20 g body weight of mice. On day 4th, mice were sacrificed with neck dislocation. Hepar cell slides were made and stained by HE. The hepar cell damage of mice were observed by counting number of necrosis cell. The data was analized by One-Way ANOVA test (? = 0.05) and continued by Post Hoc Multiple Comparisons using Least Significant Differences (LSD) test (? = 0.05). Results: The data showed that average number of necrotic nucleus of KK was 9.71; KP1 was 72.86; KP2 was 14.00; and KP3 was 22.29. The results of One-Way ANOVA test showed a significant difference in all group (p < 0.05). The statistical data result showed a significant difference of necrotic nucleus between K-KP1, K-KP2, K-KP3, KP1-KP2, KP1-KP3, and KP2-KP3 (p < 0.05). Conclusion: The feeding of mangosteen rind was able to decrease hepar cell damage of mice which is induced by paracetamol. Keywords: mangosteen rind extract, paracetamol, the damaging of hepar cell